Transcriptomic and Functional Analyses Reveal That PpGLK1 Regulates Chloroplast Development in Peach (Prunus persica) - Chen, Min; Liu, Xiao; Jiang, Shenghui; Wen, Binbin; Yang, Chao; Xiao, Wei; Fu, Xiling; Li, Dongmei; Chen, Xiude; Gao, Dongsheng; Li, Ling (Frontiers in Plant Science, 2018)
Peach is an ideal species for fruit tree research because of its small, fully sequenced genome. Chloroplast development is dependent on the tight cooperation between the nuclear and plastid genomes, and is regulated by GLK transcription factors. In this work, the pigment content was monitored and the chloroplast-to-chromoplast conversion during the fruit ripening was visualized by transmission electron microscopy. Localization and expression analyses showed that PpGLK1 was located in the nucleus and expressed mainly in the leaves and fruit skin. A transcriptome analysis showed that PpGLK1 and its target genes were significantly differentially expressed in ripening peach fruit skin. PpGLK1 silencing affected chlorophyll accumulation in peach leaves and fruits. Overexpression of PpGLK1 rescued the phenotypes of the Arabidopsis Atglk1Atglk2 double mutant and the tomato uniform ripening mutant. The results of a yeast two-hybrid analysis showed that PpGLK1 is autoactivated and that PpGLK1 (301-542 a.a.) interacted with PpARF5. Together, our results indicate that PpGLK1 regulates chloroplast development in green tissues in peach. Therefore, it may be a promising target gene for improving the production and quality of peach by genetic engineering and breeding approaches.